2020
DOI: 10.1139/as-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Boreal tree regeneration after fire and fuelwood harvesting in coastal Nunatsiavut

Abstract: Consecutive landscape-scale disturbances are known to influence boreal forest regeneration, yet few published data exist on the compounding effects of natural and anthropogenic disturbance on regeneration in subarctic forests. We conducted a dendroecological study of eastern coastal boreal forest regeneration two decades after fire at three subarctic forest stands that are important sources of fuelwood for the people of Nunatsiavut (Labrador, Canada). We quantified spruce (Picea spp.) and balsam fir (Abies bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 74 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Although wood harvesting seems to have been a primary factor affecting these forest ecosystems, some other disturbances have been observed, especially at the Dog Island site, where bark beetle outbreaks were documented during 1790, 1910, 1920and 1970-2000(Roy et al 2017. At the Nain site, no evidence of insect damage or fire was found (Lemus-Lauzon et al 2018) and no evidence of fire was noted at Kammasûk and Webb's Bay although a forest fire of moderate size did occur in the latter region in 2004 (Brehaut and Brown 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although wood harvesting seems to have been a primary factor affecting these forest ecosystems, some other disturbances have been observed, especially at the Dog Island site, where bark beetle outbreaks were documented during 1790, 1910, 1920and 1970-2000(Roy et al 2017. At the Nain site, no evidence of insect damage or fire was found (Lemus-Lauzon et al 2018) and no evidence of fire was noted at Kammasûk and Webb's Bay although a forest fire of moderate size did occur in the latter region in 2004 (Brehaut and Brown 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At WB, loss of permafrost following fire is modelled to occur at least 24 years earlier when compared to undisturbed simulations, at a rate that is three to four times faster than that reported for the West. This accelerated degradation is likely due to the warmer, less ice-rich permafrost (i.e., with lower latent heat) at our site compared to conditions in the central Northwest Territories (Smith et al 2015) and may also reflect the slower post-fire forest regeneration processes reported for WB (Brehaut and Brown 2020) compared to the pulse recruitment that has been documented following fire in the West (Johnstone et al 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Our simulations relate to ground conditions at a burned site located on a north-facing slope along Webb Bay (WB; 56.706°N, 62.209°W), ~25 km northwest of Nain (Figure 1-C). The WB burn was a small (1 km 2 ) low severity fire that occurred in summer 2004 (Brehaut and Brown 2020). The site is located on a series of raised beaches, although erratics are also present.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, interest in quantitatively characterizing forest successional dynamics is increasing . Empirical models, such as logistic (e.g., Taylor and Chen 2011;Boucher et al 2014), linear (e.g., Bose et al 2014;Brehaut and Brown 2020) and nonlinear (e.g., Brown et al 2015) mixed effects, and Markov (e.g., Baasch et al 2010), are widely used with observational data. Mechanistic models rely on knowledge of underlying ecological processes to simulate succession (e.g., Boulanger et al 2018Boulanger et al , 2019.…”
Section: Introductionmentioning
confidence: 99%